Entrepreneurial intention of students reviewed from self-efficacy and family support in vocational high school - Fatwa Tentama; Tri Hartina Paputungan (Institute of Advanced Engineering and Science, 2019)
Self-efficacy and family support is one of the factors associated with entrepreneurial intentions in Vocational High School students. This study aims to examine empirically the role of self-efficacy and family support towards entrepreneurial intentions in students of Vocational High Schools. The subjects of this study are students of class XII of State Vocational High School 5 Yogyakarta. The sampling technique was randomized using cluster random sampling technique. Methods of collecting data are the scale of self-efficacy, family support scale, and scale of entrepreneurial intention. Analysis of research data is conducted by using multiple linear regression techniques. The results showed that 1) there was a very significant relationship between self-efficacy and family support simultaneously with entrepreneurial intentions indicated by a significance value of p = 0.001, 2) there was a very significant positive relationship between self-efficacy and entrepreneurial intention with a significance value of p = 0.000, 3) there was a significant positive relationship between family support and entrepreneurial intentions with a significance level of p = 0.045. Self-efficacy and family support together contributed 8.6%. Self-efficacy as an internal factor contributes more dominantly than family support as an external factor. The effective contribution of self-efficacy with entrepreneurial intentions was 8.032% and the contribution of family support with entrepreneurial intentions was 0.611%.